Function of Epirubicin-Conjugated Polymeric Micelles in Sonodynamic Therapy - Takemae, Kazuhisa; Okamoto, Jun; Horise, Yuki; Masamune, Ken; Muragaki, Yoshihiro (Frontiers in Pharmacology, 2019)
The combinatory use of high-intensity focused ultrasound (HIFU) and epirubicin (EPI)-conjugated polymeric micellar nanoparticles (NC-6300) is thought to be a less invasive and more efficient method of cancer therapy. To investigate the mechanism underlying the combination effect, we examined the effect of trigger-pulsed HIFU (TP-HIFU) and NC-6300 from the perspective of reactive oxygen species (ROS) generation, which is considered the primary function of sonodynamic therapy (SDT), and changes in drug characteristics. TP-HIFU is an effective sequence for generating hydroxyl radicals to kill cancer cells. EPI was susceptible to degradation by TP-HIFU through the production of hydroxyl radicals. In contrast, EPI degradation of NC-6300 was suppressed by the hydrophilic shell of the micelles. NC-6300 also exhibited a sonosensitizer function, which promoted the generation of superoxide anions by TP-HIFU irradiation. The amount of ROS produced by TP-HIFU reached a level that caused structural changes to the cellular membrane. In conclusion, drug-conjugated micellar nanoparticles are more desirable for SDT because of accelerated ROS production and drug protection from ROS. Furthermore, a combination of NC-6300 and TP-HIFU is useful for minimally invasive cancer therapy with cooperative effects of HIFU-derived features, antitumor activity of EPI, and increased ROS generation to cause damage to cancer cells.